Effect of ozone on conidia of Sphaerotheca fuliginea - MUJEEBUR RAHMAN KHAN, M. WAJID KHAN and (Indian Phytopathology, 2002)
Effect of 0.2 ppm 03 for 3, 6, 9 and 12 hours exposure durations on size, germination and fibrosin bodies of conidia of Sphaeotheca fuliginea was studied in artificial treatment conditions. The conidia exposed to 03 for 12 hours were deshaped and their walls ruptured. Ozone caused significant decrease in size (length and width) of conidia and number of fibrosin bodies in 6-12 h. treatments. Per cent germination of conidia was gradually inhibited with the increase in exposure duration.